Hepatic veno-occlusive disease as a result of a traditional remedy: confirmation of toxic pyrrolizidine alkaloids as the cause, using an in vitro technique. Issue 9 (1st September 2002) - Zuckerman, M; Steenkamp, V; Stewart, M J
Abstract : Background/Aims: A child presented with hepatic veno-occlusive disease after having been administered a short course of treatment with a traditional herbal remedy. The child subsequently died. Postmortem liver histology confirmed the diagnosis. This study aimed to investigate the hypothesis that the herbal remedy was the cause of veno-occlusive disease. Methods: Extracts of the traditional remedy were analysed by colorimetry and gas chromatography/mass spectrometry. Cultured hepatocytes were treated with an extract of the plant material and examined for morphological changes. Results: The screening analyses indicated the presence of toxic pyrrolizidine alkaloids, which were later confirmed by gas chromatography/mass spectrometry. The cell studies indicated dose related toxicity, with necrosis at high concentrations and apoptosis and abnormalities of the cytoskeleton at lower concentrations. Conclusions: The simple screening techniques used allowed rapid confirmation of the presence of toxic pyrrolizidines in the remedy. The in vitro method confirmed the toxicity of herbal extracts to hepatocytes.